Elevator pitch : a novel - Barclay, Linwood (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"The New York Times bestselling author of A Noise Downstairs and No Time for Goodbye returns with an edge-of-your-seat thriller that does for elevators what Psycho did for showers and Jaws did for the beach--a heart-pounding tale in which a series of disasters paralyzes New York City with fear. Pulsating with tension, Elevator Pitch is a riveting tale of psychological suspense that is all too plausible. and will chill readers to the bone"--